Studi Numerik Performa Rangka Bresing Eksentrik Link Vertikal Profil Tubular - Dzul Fikri Muhammad; Budi Suswanto (Jurnal Aplikasi Teknik Sipil, 2020)
Eccentrically Braced Frames (EBF) have been used as earthquake suppression systems, especially in buildings. This system relies on yielding at link on the main beam which is located between the eccentric bracing (EBH). EBH has important weaknesses to review. In the event of an earthquake that causes the link beam to rotate vertically, causing the structure above the beam damaged. Also it is not easy to repair the beam link at EBH after a severe earthquake. To overcome the problems in the EBH system, a new system was proposed, called Vertical-EBF (EBV). Links with WF and tubular profiles are two profiles commonly used in structures. In this research, EBF specimen modeling with tubular profile vertical links was compared with EBF horizontal links. The results showed a structure with EBV had a lighter weight.Yielding only occur at link so its better for earthquake rehabilitation.